Depression, Anxiety, Stress, Associated with Lichen Planus in Jordanian Women and the Impact on Their Quality of Life - Alnazly E; Absy N; Sweileh I (Dove Medical Press, 2023)
Eman Alnazly,1 Nadine Absy,2 Ibrahim Sweileh3 1Faculty of Nursing, Al-Ahliyya Amman University, Amman, Jordan; 2Al Hussain New Salt Hospital, Amman, Jordan; 3Florida Gulf Coast University, Health Science Department, Fort Myers, FL, USACorrespondence: Eman Alnazly, Faculty of Nursing, Al-Ahliyya Amman University, Amman, 19328, Jordan, Tel +966 5 3500211/217 Ext. 2593/4502, Fax +00962 -6- 5335169, Email emanalnazly@hotmail.comPurpose: To identify mental health problems in patients with lichen planus (LP). We evaluated the impact of LP on patients' mental health and quality of life and the associations with sociodemographic and clinical characteristics.Materials and Methods: This cross-sectional study was conducted in Amman, Jordan, between August 2022 and May 2023. We conducted a survey of 126 women with LP mean age of 48.61 years and a standard deviation of 15.25 years. The survey included sociodemographic characteristics, the Arabic version of the Dermatology Life Quality Index (DLQI), and the 21-item Depression, Anxiety, and Stress scale.Results: The DLQI scores indicated that LP had substantial effects on the quality of life of most of the participants (63.5%), and the condition was significantly correlated with depression (r = 0.381), anxiety (r = 0.469), and stress (r = 0.475). Longer disease duration and misdiagnosis prior to LP diagnosis were also significantly correlated with quality of life (r = 0.388 and r = 0.317, respectively), as were the LP symptoms. The most robust correlation coefficients were observed for itching symptoms and location in the genital area (r = 0.277 and r = 0.354), respectively.Conclusion: Depression, anxiety, and stress can significantly reduce the quality of life among patients with LP. This study proves the need for healthcare providers to consider interventions that improve the psychological well-being and QOL of patients. Additionally, this study highlights the importance of the implementation of evidence-based practice to improve the timely diagnosis of LP. It is essential to follow a comprehensive approach when diagnosing and treating LP. This involves a multidisciplinary collaboration between different specialties as well focusing on patient education.Keywords: dermatology life quality index, mental health, psychological distress, autoimmune disease, skin disease